Análise teórica das propriedades estruturais, eletrônicas, energéticas e ópticas dos defeitos substitucionais Cu e Ag no composto Li2B4O7 - Santos, Cledson dos (2018)
The structural, electronic, energetic and optical properties of the compound Li2B4O7 containing the substitutional defects Cu or Ag were investigated by means of calculations of first principles at the Density Functional Theory level using the LAPW method implemented in the computer code Wien2k. The isolated Cu and Ag defects are considered in four charge states (q = -1, 0, +1, +2) with objective to simulate situations of the capture of an electron or a hole. In all cases, the atomic positions are computationally relaxed, Cu – O and Ag – O chemical bonds nature carefully analyzed and local structure around the defects determined. It is found that the defects vastly perturbs its neighborhood and the Cu and Ag themselves exhibit significant off-site dislocation from initial Li position in their Cu1+ and Ag1+ charge states, which becomes especially more pronounced for the Cu0 and Ag0 defects. Only the Cu2+ and Ag2+ centers stabilize at the substitutional Li site. Resulting defect formation energies demonstrate that the Cu1+, Cu0, Ag1+, and Ag0 centers are the most stable ones. Electronic structure calculations reveal that the Cu and Ag ions introduce their d- and s-states within the gap and their energies and occupation depend strongly on the charge state of the defect. Experimental optical absorption spectra are well reproduced by the Cu1+ and Ag1+ defects spectra, leading to the conclusion that in the as-grown material just Cu1+ and Ag1+ centers are formed. In the case of irradiated compound, present study predicts formation of the interstitial Cu0 defects, whose presence should significantly change the optical absorption and emission of the material, as well as demonstrates the presence of new absorption peaks associated with the interstitial Ag0 and substitutional Ag2+ centers, which reasonably describe the experimental spectrum.